Reverse engineering a hierarchical regulatory network downstream of oncogenic KRAS - Iwona Stelniec‐Klotz; Stefan Legewie; Oleg Tchernitsa; Franziska Witzel; Bertram Klinger; Christine Sers; Hanspeter Herzel; Nils Blüthgen; Reinhold Schäfer (Molecular Systems Biology)
Abstract RAS mutations are highly relevant for progression and therapy response of human tumours, but the genetic network that ultimately executes the oncogenic effects is poorly understood. Here, we used a reverse‐engineering approach in an ovarian cancer model to reconstruct KRAS oncogene‐dependent cytoplasmic and transcriptional networks from perturbation experiments based on gene silencing and pathway inhibitor treatments. We measured mRNA and protein levels in manipulated cells by microarray, RT–PCR and western blot analysis, respectively. The reconstructed model revealed complex interactions among the transcriptional and cytoplasmic components, some of which were confirmed by double pertubation experiments. Interestingly, the transcription factors decomposed into two hierarchically arranged groups. To validate the model predictions, we analysed growth parameters and transcriptional deregulation in the KRAS‐transformed epithelial cells. As predicted by the model, we found two functional groups among the selected transcription factors. The experiments thus confirmed the predicted hierarchical transcription factor regulation and showed that the hierarchy manifests itself in downstream gene expression patterns and phenotype.